We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
864
11
avatar+1832 

How he made this ! 

 

 Feb 3, 2015

Best Answer 

 #2
avatar+23357 
+15

How he made this !

$$\int {\frac{1}{\sqrt{4-(x-3)^2}} }\ dx
=\int
\frac{1}{\sqrt{4[ 1- \left( \frac{x-3}{2} \right)^2} ] }\ dx
=\frac{1}{2}\int
\frac{1}{\sqrt{1- \left( \frac{x-3}{2} \right)^2}}\ dx\\\\
\small{\text{We substitute:
$
\frac{x-3}{2}=\sin{(u)},
$
so we have
$
\frac{1}{2}\ dx=\cos{(u)}\ du
$
or
$
\ dx=2\cos{(u)}\ du
$
}}\\
=\frac{1}{2}\int
\frac{2\cos{(u)}}{\sqrt{1- \sin^2{(u)}}}\ du
=\frac{1}{2}\int
\frac{2\cos{(u)}}{\cos{(u)}}}\ du
=\int\ du=u\\
\small{\text{We substitute back:
$
u=\arcsin{ ( \frac{x-3}{2} ) }
$
}}\\\\
\int {\frac{1}{\sqrt{4-(x-3)^2}} }\ dx =\sin^{-1}{ ( \frac{x-3}{2} ) }$$

.
 Feb 3, 2015
 #1
avatar+104963 
+15

 

 

-5 + 6x - x^2 =

-5 - (x^2 - 6x )          complete the square on x...take one-half the coefficient on x

(= 3), square it (= 9)....then......add and subtract it...so we have...

-5 - (x^2 - 6x + 9 - 9) =

-5 + 9 - (x^2 - 6x + 9)       factor  the expression on the parenthesis

4 - (x - 3)^2

And that's it...

 

 Feb 3, 2015
 #2
avatar+23357 
+15
Best Answer

How he made this !

$$\int {\frac{1}{\sqrt{4-(x-3)^2}} }\ dx
=\int
\frac{1}{\sqrt{4[ 1- \left( \frac{x-3}{2} \right)^2} ] }\ dx
=\frac{1}{2}\int
\frac{1}{\sqrt{1- \left( \frac{x-3}{2} \right)^2}}\ dx\\\\
\small{\text{We substitute:
$
\frac{x-3}{2}=\sin{(u)},
$
so we have
$
\frac{1}{2}\ dx=\cos{(u)}\ du
$
or
$
\ dx=2\cos{(u)}\ du
$
}}\\
=\frac{1}{2}\int
\frac{2\cos{(u)}}{\sqrt{1- \sin^2{(u)}}}\ du
=\frac{1}{2}\int
\frac{2\cos{(u)}}{\cos{(u)}}}\ du
=\int\ du=u\\
\small{\text{We substitute back:
$
u=\arcsin{ ( \frac{x-3}{2} ) }
$
}}\\\\
\int {\frac{1}{\sqrt{4-(x-3)^2}} }\ dx =\sin^{-1}{ ( \frac{x-3}{2} ) }$$

heureka Feb 3, 2015
 #3
avatar+1832 
+5

But where is my mistake here 

 

 Feb 5, 2015
 #4
avatar+104963 
+10

Let's go from this step

-(x^2 -6x + 9 - 9) - 5    =

-(x^2 - 6x + 9) +  9 - 5  =

-(x - 3)^2 + 4  =

4 - (x - 3)^2

 

 Feb 5, 2015
 #5
avatar+1832 
+5

But why we cant multiply the negative sign inside the parentheses in this step 

-(x^2 - 6x + 9) +  9 - 5

 

so its become 

(-x^2 + 6x - 9) + 9 - 5

 Feb 6, 2015
 #6
avatar+105683 
+10

You mistake is that

$$(x-3)^2=x^2-6x+9\\\\
$It does not equal $-x^2+6x-9\\\
$that is why -1 had to be left out of the bracket!$$$

.
 Feb 6, 2015
 #7
avatar+104963 
+5

Thanks, Melody.....

 

 Feb 6, 2015
 #8
avatar+105683 
+5

My pleasure Chris :)

 Feb 6, 2015
 #9
avatar+1832 
0

Melody 

I don't get it 

$$-x^2+6x-9$$ = $$(x-3)^2$$

Also 

$$x^2-6x+9 = (x-3)^2$$

 

so what is wrong !!! 

 Feb 18, 2015
 #10
avatar+105683 
+5

NO

$$-x^2+6x-9$$  does not equal      $$(x-3)^2$$      

 

 

$$\\-x^2+6x-9= -(x^2-6x+9)=-1*(x^2-6x+9) = -1*(x-3)^2\\\\
$the -1 is not squared so$ \\\\
(x-3)^2 \ne -x^2+6x-9$$

 

remember 

    $$-3^2\ne(-3)^2$$

 

consider these two sums

$$20+-3^2 = 20-3^2=20-9=11$$

and

$$20+ (-3)^2 = 20++9=29$$

 

see        $$-3^2\ne(-3)^2$$

 

I hope that helps :)

 Feb 18, 2015
 #11
avatar+1832 
+5

Now its clear .. thank you 

 Feb 18, 2015

17 Online Users